The politics of exile - Dauphinee, Elizabeth (New York : Routledge, 2013)
"Written in an autoethnographical narrative form, The Politics of Exile offers a unique insight into the complex encounter of researcher with research subject, in the context of the Bosnian War and its aftermath. Bringing theory to life and giving a wide range of concepts in international relations a corporeal reality, Dauphinee uses her own experiences to shed light on the often difficult position of new academics and junior researchers and their struggles to get their foot in the intellectual door of the field"--
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Dauphinee, Elizabeth; Yugoslav War, 1991-1995 -- Atrocities -- Bosnia and Hercegovina; Yugoslav War, 1991-1995 -- Moral and ethical aspects -- Bosnia and Hercegovina; War -- Fieldwork -- Moral and ethical aspects; Research -- Moral and ethical aspects; College teachers -- Canada -- Biography; Electronic books